PENANAMAN KEDISIPLINAN MAHASISWA PADA MATA KULIAH PERKEMBANGAN PESERTA DIDIK - Hangestiningsih, Endang; Lelana, Endah Sari (TAMAN CENDEKIA: Jurnal Pendidikan Ke-SD-an, 2018)
This research aims to describe the disciplinary cultivation in the Development of Learners course of college students majoring in Primary Teacher Education. The disciplinary cultivation is conducted through several ways, namely lecturers and students make an agreement together, lecturers become the role model, lecturers motivate and guide the students, lecturers as partners, and also lecturers give freedom to the students but limited to the rules that is governed. The method of this research uses qualitative research so that it is able to give an overview of social situation in depth. The research results describe that the methods implemented by the lecturers are successful in increasing the students’ disciplinary in the course of Development of Learners for college students majoring in Primary Teacher Education.